2015
DOI: 10.1093/asj/sjv106
|View full text |Cite
|
Sign up to set email alerts
|

Microbiologic Safety of the Transareolar Approach in Breast Augmentation

Abstract: During transareolar breast augmentation, in the nipple-areola region it is more likely to find bacteria populating the skin, rather than endogenous breast flora, as previously considered. Appropriate preoperative decontamination is essential for minimizing the risk of postoperative infections. LEVEL OF EVIDENCE 3: Risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…We thank Dr Bartsich for providing valuable input on our previously reported work 1 and we agree with her conclusion: the breast cannot be considered a sterile site. 2 As the human body includes 10 times more bacterial cells than human cells, 3 it is virtually impossible for any particular bodily compartment which communicates with the exterior to be sterile.…”
supporting
confidence: 78%
“…We thank Dr Bartsich for providing valuable input on our previously reported work 1 and we agree with her conclusion: the breast cannot be considered a sterile site. 2 As the human body includes 10 times more bacterial cells than human cells, 3 it is virtually impossible for any particular bodily compartment which communicates with the exterior to be sterile.…”
supporting
confidence: 78%
“…A 2016 microbiological study of cultures obtained from breast skin and parenchyma at surgery found that the cultured organisms are not distinct from ordinary skin flora, and that the periareolar approach is microbiologically safe. 31 A specific microbiome or organism has not been linked to capsular contracture. Bacterial profiles are patient-specific rather than disease-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Under ordinary sterile surgical technique, there is no opportunity for contamination other than by resident microorganisms on the skin and in the breast. A 2016 microbiological study found that the skin bacteria and breast parenchymal microorganisms are similar 38 . A sophisticated microbiological study published in 2019 failed to identify a specific bacterium that is linked to capsular contracture 39 .…”
Section: Discussionmentioning
confidence: 99%